2014
DOI: 10.18632/oncotarget.2219
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy promotes replication of oncolytic Newcastle disease virus by blocking intrinsic apoptosis in lung cancer cells

Abstract: Apoptosis contributes to antitumor effect of Newcastle disease virus (NDV). Autophagy is a protective response under cellular stress including viral infection. How autophagy interferes with oncolysis of NDV remains unclear. In this study, we found that NDV La Sota strain induced autophagy and preserved autophagic flux in non-small cell lung cancer cells. NDV-induced autophagy promoted viral replication by blocking cancer cells from caspase-dependent apoptosis. Moreover, we found that NDV recruited SQSTM1-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 39 publications
1
48
0
1
Order By: Relevance
“…The inhibition of apoptosis by mitophagy favors viral replication and promotes the pathogenesis of viral infection [56]. Similar findings have been reported with HBV, HCV, VEEV, CSFV, PRRSV, Newcastle disease virus (NDV), and transmissible gastroenteritis virus (TGEV) [35,37,38,40,41,57,58]. These examples share 2 concurrent phenomena: (1) upon infection, viruses induce mitophagy via different mechanisms, and (2) subsequent mitophagy mitigates apoptosis to promote viral infection.…”
Section: Virus-triggered Mitophagy Inhibits Apoptosis For Viral Replisupporting
confidence: 57%
“…The inhibition of apoptosis by mitophagy favors viral replication and promotes the pathogenesis of viral infection [56]. Similar findings have been reported with HBV, HCV, VEEV, CSFV, PRRSV, Newcastle disease virus (NDV), and transmissible gastroenteritis virus (TGEV) [35,37,38,40,41,57,58]. These examples share 2 concurrent phenomena: (1) upon infection, viruses induce mitophagy via different mechanisms, and (2) subsequent mitophagy mitigates apoptosis to promote viral infection.…”
Section: Virus-triggered Mitophagy Inhibits Apoptosis For Viral Replisupporting
confidence: 57%
“…Some other viruses, such us Hepatitis B and C virus (HBV and HCV) New Castle Disease virus (NDV) and measles viruses, induce instead mitochondrial fission and mitophagy which also favour viral replication [73][74][75][76]. Also the Influenza A (subtype H1N1) full-length PB1-F2 protein targets MT and causes loss of mitochondrial membrane potential and mitochondrial fragmentation [77].…”
Section: Mitochondria Fusion Governs Innate Immunitymentioning
confidence: 99%
“…In the early stages of infection, viruses need tumor cells to be alive so they can take over and control the cellular molecular cell death machinery, but at later periods of infection, oncolytic viruses lyse and kill tumor cells to release newly assembled viruses (2). Some studies have reported that apoptosis limits the replication of influenza virus and other viruses (37)(38)(39)(40), but others have found that promoting apoptosis activates the replication of human herpes virus and hepatitis B virus (41,42). We found that neither pan-caspase inhibitors (Z-VAD-FMK and Q-VD-Oph) nor a JNK inhibitor (SP600125) abrogated the combined cytotoxicity (Fig.…”
Section: Discussionmentioning
confidence: 99%